No.209 Remittance Investment Climate Analysis: Framework and Methods to Ascertain the Local Development Potential of Overseas Remittances - Ang, Alvin P (Archīum Ateneo, 2020)
This paper presents the integrated mixed methods results and findings of four community-based studies on the local development potential of overseas remittances.We developed a Remittance Investment Climate (ReIC) analytical framework that outlines what the rural origins of overseas migrants need to see for their remittances to make productive contributions locally. This ReIC framework was piloted through a mixed methods tool called the Remittance Investment Climate Analysis in Rural Hometowns (RICART) and was conducted over a four-year period in four rural municipalities in the Philippines. The interactions between remittance owners (remitters abroad and their families) and their rural hometowns’ investment climate conditions were analyzed. The results and findings on remittances being saved, invested and parked as operational enterprises locally are contextualized per municipality.We find that the interventions by local authorities to improve investment conditions are important actions, but so are improving rural residents’ financial literacy levels, and their practices surrounding financial inclusion and financial functioning. The local development potential of remittances thus rests on conjoint actions to improve local investment climate conditions and regulations, and the financial capabilities of rural residents.